MODERN REHABILITATION INTERVENTIONS IN CHILDREN WITH VARIOUS FORMS OF CEREBRAL PALSY USING, LEVITAS AND K-FLEX TRAINING DEVICES (International journal of medical sciences, 2026)
Cerebral palsy (CP) is a term describing a group of heterogeneous conditions that cause non-progressive spasticity, ataxia, or involuntary movements; it is not a single specific disease (1). CP is a polyetiological disorder. The leading cause of CP development is damage to or abnormal development of the brain of the fetus or newborn. The pathophysiological basis of CP formation is brain injury occurring during a specific period of its development, followed by the formation of pathological muscle tone (predominantly spasticity), with preservation of postural reflexes and impaired development of sequential righting and equilibrium reflexes. The main difference between CP and other central paralyses lies in the timing of exposure to the pathological factor. The ratio of prenatal and perinatal factors in brain injury in CP is of significant importance (2).